Proposição de indicadores para o gerenciamento de resíduos sólidos em uma Instituição de Ensino Superior (IES) - Alcântara Filho, José Airton Gomes de (2023)
The unbridled production and irregular disposal of solid waste bring health, social and environmental problems to humanity. In Brazil, the issue began to be faced incisively after the National Solid Waste Policy of 2010. The Universidade Federal do Ceará (UFC), for generating large volumes of various types of waste, needs to have an effective management of its solid waste. The adoption of performance indicators for solid waste management is an important tool for improving management at the institution. The rationale discusses sustainability, indicators and current concepts on solid waste management to preserve the environment. The general objective of the research is to propose a set of solid waste management indicators for the UFC to promote social and economic sustainability. As for the methodological aspects, the research is developed through bibliographical and documentary research, of an applied nature, of the descriptive and qualitative type. As a result, the research proposes a set of 15 indicators that managers directly related to solid waste management at UFC approved regarding relevance, data accessibility and calculation method. The indicators were analyzed and completed, according to data available at the Institution and collected directly by the survey. The analysis of the indicators showed, for example, that around 1% of the UFC's budget is related to solid waste management. The survey concluded with the suggestion that the indicators be continuously used to improve waste management at UFC.